Characterization of the complete plastome of Dendrophthoe pentandra (Loranthaceae), a stem hemiparasite - Guo, Xiaorong (Mitochondrial DNA B Resour, 2019)
Dendrophthoe pentandra (Linnaeus) Miquel (Loranthaceae) is a stem hemiparasite distributed in southwest China and Indochina. Here, we present the first complete plastome of the plant. The plastome is 115,721 bp in length, and encodes 92 unique genes, including 63 protein-encoding gens, 4 rRNAs, and 25 tRNAs. Phylogenetic analysis indicated that D. pentandra is close to Macrosolen cochinchensis (Loureiro) Tieghem and Helixanthera parasitica Loureiro.